Oxygen Transport to Tissue XXXVIII - Luo, Qingming; Li, Lin Z.; Harrison, David K.; Shi, Hua; Bruley, Duane F. (Advances in Experimental Medicine and Biology, 2016)
This book contains the refereed contributions from the 43rd annual meeting of ISOTT. The annual meetings of ISOTT bring together scientists from various fields (medicine, physiology, mathematics, biology, chemistry, physics, engineering, etc.) in a unique international forum. ISOTT conferences are a place where an atmosphere of interaction is created, where many questions are asked after each presentation and lively discussions occur at a high scientific level. This vivid interaction is the main motivation for members to participate and gain new ideas and knowledge in the broad field of oxygen transport to tissue. The proceedings include sessions covered various research topics including Multi-Modal Imaging/Spectroscopy & Instrumentation; Cancer Metabolism; Cellular Hypoxia and Mitochondrial Function; Brain Oxygenation and Function; Other Organ Function and Metabolism; Oxygen Transport in Sports, Diseases and Clinical Care; Acupuncture, Meridians, and Primo Vascular System; EPR, MRS and MRI.